Answer: d - (d x .1)
Step-by-step explanation: The expression that will show how much the actor will earn is d - (d x .1). D is the actor’s earnings and d x .1 is the commission of their agent.
Hahahhahshhshshshsjsmsnbdbdmdmmsorry
Answer:
I think that it is c or a
Step-by-step explanation:
i have no explanation i just think that it is c or a
2x+y=5
y+3=2x
y+3-3 = 2x-3
y= 2x -3
2x + y =5
2x + 2x -3 = 5
Answer:
g(x) = x+1
Step-by-step explanation:
Informally, you can see that the function h(x) takes the root of a value that is 1 more than the value under the same radical in f(x). This suggests that adding 1 to x in f(x) will give you h(x). That is, ...
h(x) = f(x+1) = f(g(x))
so
g(x) = x+1
_____
More formally, you can apply the inverse of the function f(x) to the equation ...
h(x) = f(g(x))
f^-1(h(x)) = f^-1(f(g(x))) . . . inverse function applied
f^-1(h(x)) = g(x) . . . . . . . . . simplified
Now f^-1(x) can be found by solving for y in ...
x = f(y)
x = ∛(y+2) . . . . . . . . . definition of f(y)
x^3 = y+2 . . . . . . . . . cube both sides
x^3 -2 = y = f^-1(x) . . . subtract 2 from both sides
So, f^-1(h(x)) is ...
f^-1(h(x)) = g(x) = (∛(x+3))^3 -2 = x+3 -2
g(x) = x+1